2020
DOI: 10.1037/drm0000128
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative text analysis approach to describing posttrauma nightmares in a treatment-seeking population.

Abstract: The interpretation of dreams has been a topic of interest for many centuries, dating back to 350 BC (Aristoteles, 2001). Specific considerations of the meaning of nightmares have not been as richly developed as they have been for dreams. One way dream researchers have analyzed dreams is through examining the use of language in dream reports. However, this method is in its infant stages regarding its approach to understanding nightmares. Psychological constructs can be measured using a form of quantitative text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Most aggressors in nightmares are, incidentally, male perpetrators (Schredl & Göritz, 2018). Post-trauma nightmares, compared with typical dreams, have reduced leisure word counts and increased risk words, as well as higher rates of singular first-person pronouns (Paquet et al, 2020). Notably, "finding money" and "eating delicious foods" are both positive typical dream themes (Nielsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Most aggressors in nightmares are, incidentally, male perpetrators (Schredl & Göritz, 2018). Post-trauma nightmares, compared with typical dreams, have reduced leisure word counts and increased risk words, as well as higher rates of singular first-person pronouns (Paquet et al, 2020). Notably, "finding money" and "eating delicious foods" are both positive typical dream themes (Nielsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…[17] Ref. [13] classification effect for recessive expressions is poor. e proposed model integrates CNN, BiGRU, and attention mechanism and extracts the semantic features of the text from bottom to top through "word-sentence-text."…”
Section: Proposed Modelmentioning
confidence: 98%
“…Text sentiment analysis refers to the use of computers to automatically calculate and process human natural language texts, involving comprehensive problems in mathematics, statistics, and computational science. Its goal is to solve the problem of computer and text sentiment analysis in order to maximize the extraction of valuable information and achieve better human-computer interaction [13].…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, LIWC has been used to describe and analyze post‐trauma nightmares—or PTNM (Paquet et al, 2020a, 2020b). Paquet et al (2020a) found that the PTNM of a treatment‐seeking sample, relative to dreams in a nonclinical sample, contain more references to negative emotions and perceptual experiences, as well as are considered to have less of an analytic nature. Additionally, there were no differences detected between PTNM and dreams in the use of cognitive language.…”
Section: Introductionmentioning
confidence: 99%